The impact of surface waves of South American earthquakes on the ice sheet of the Antarctic Peninsula - Gryn, Dmytro; Liashchuk, Oleksandr; Otruba, Yurii; Andrushchenko, Yuriy (Ukrainian Antarctic Journal, 2024)
Earthquakes cause fluctuations in the surface of the geological environment, which may affect Antarctica’s ice sheet. As seismic waves interact with a glacier, more fissures appear, and its speed may increase. These processes may accelerate the reduction in the total mass of the West Antarctic ice cover. We analysed the physical impact of earthquakes registered at the Ukrainian Antarctic Akademik Vernadsky station on some local glaciers. We also aimed to indirectly identify the consequences of the destruction of the integrity of the glacier structure, which are accompanied by the appearance of induced seismicity. The most characteristic wave fields from various seismically active tectonic zones around Galindez Island were selected to analyse glacier response to earthquake-related seismic forces. We analysed the acceleration of the ground’s surface for short-term earthquakes and the time during which these seismic waves were acting on the local glaciers. Seismic data from the most distant earthquake in Peru, magnitude 7.2, which occurred on May 26, 2022, at 12:02:21 UTC, were used to avoid the cumulative effect of P waves, S waves, and surface waves. Seismic waves of different types arrive at the observation point at different times due to the large distance from the source and different rates of wave propagation. This separation allows us to study the interaction of each type of wave and the glacier individually. This publication reports our analysis of the effect of a long-period surface wave on glaciers near Galindez Island. Induced cryoseismicity manifests itself in the high-frequency region of seismic records as a series of pulses associated with the formation of ice cracks. We used the data from the Guralp CMG 40-TDE seismic station, currently the only one at the Akademik Vernadsky station. The available seismic data made it possible to identify the cause-and-effect relationship between teleseismic waves from tectonic earthquakes and local cryoseismicity. However, the data from a single station do not allow for locating cryoseismic sources. We also analysed the characteristic local interference wave fields that complicate detecting target waves.